Transformational Leadership’s Influence on Human Resource Performance via Organizational Climate and Commitment - Tovan; Armawati; Mutmainah; Salma D (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to examine the impact of transformational leadership on human resource performance through organizational climate and organizational commitment in the Morowali Regency Government, using a sample of 77 respondents and data collected through questionnaires and analyzed using PLS (Partial Least Square) software. The findings of this study indicate that there is a significant influence of transformational leadership on organizational climate and organizational commitment and that organizational climate has a significant influence on employee performance. At the same time, organizational commitment had no significant effect on employee performance in the Morowali Regency Government.